Cytogenetics of Oryctes nasicornis L. (Coleoptera: Scarabaeidae: Dynastinae) with Emphasis on Its Neochromosomes and Asynapsis Inducing Premature Bivalent and Chromosome Splits at Meiosis - B. Dutrillaux; A. M. Dutrillaux (Psyche: A Journal of Entomology)
The chromosomes of specimens of Oryctes nasicornis from three locations in France and two locations in Greece were studied. All karyotypes have an X-Y-autosome translocation: 18, neoXY. Two male specimens from France (subspecies nasicornis) displayed an unusual behaviour of their meiotic chromosomes in 30–50% of spermatocytes, with asynapsis at pachynema, premature bivalent and chromosome split at metaphases I and II. The karyotypes remained balanced at metaphase I, but not at metaphase II. These particularities mimic the meiotic behaviour of B chromosomes and question about their existence, reported earlier in Spanish specimens. Due to the variable character of B chromosomes, complementary analyses are needed. To our knowledge, such meiotic particularities have not been described, beside cases of infertility. In specimens from Corsica (subspecies laevigatus) and Greece (subspecies kuntzeni), all spermatocytes I and II had a normal appearance. The meiotic particularity may thus be limited to male specimens from subspecies nasicornis.